Some New Oscillation Criteria for a Class of Nonlinear Fractional Differential Equations with Damping Term - Bin Zheng; Qinghua Feng (Journal of Applied Mathematics)
We are concerned with oscillation of solutions of a class of nonlinear fractional differential equations with damping term. Based on a generalized Riccati function and inequality technique, we establish some new oscillation criteria for it. Some applications are also presented for the established results.